The effects and mechanism of taxanes on chemotherapy-associated ovarian damage: A review of current evidence - Wu, Chuqing; Wu, Tong; Chen, Dan; Wei, Simin; Tang, Weicheng; Xue, Liru; Xiong, Jiaqiang; Huang, Yibao; Guo, Yican; Chen, Ying; Wu, Meng; Wang, Shixuan (Frontiers in Endocrinology, 2022)
Chemotherapy is often a cause of premature ovarian insufficiency and infertility since the ovarian follicles are extremely sensitive to the effects of chemotherapeutic agents. Different chemotherapeutic agents with varying mechanisms of action may damage ovarian function differently. Taxanes are widely used in clinical cancer treatment, but the specific reproductive toxicological information is still controversial. This review described the impact and duration of taxanes on ovarian function in women and analyzed the possible reasons for different conclusions. Furthermore, the toxicity of taxanes on ovarian function and its possible mechanisms were discussed. The potential protective strategies and agents against ovarian damage induced by taxanes are also reviewed.